Analisis Kelayakan Usaha Sapi Potong Di Kecamatan Lemahsugih Kabupaten Majalengka - Malik Maulana, Rivaldi; Somanjaya, Rachmat; Adam Yuliandri, Lili (Tropical Livestock Science Journal, 2024)
This study aims to measure the level of income and analyze the feasibility of the business and determine the factors that affect the income of beef cattle farmers in Lemahsugih District, Majalengka Regency. The research was conducted by surveying beef cattle farmers in Lemahsugih District, Majalengka Regency for two months from November to December 2023. A total of 66 respondents were determined by purposive sampling based on the number of active farmers through the calculation of the Slovin formula. Data collection, both primary and secondary, was conducted by observation and interview or using a questionnaire. The data obtained were analyzed descriptively, evaluated for business feasibility, and analyzed using multiple linear regression to determine how much the factors that have been determined can affect the income of farmers. The results showed that beef cattle farming in Lemahsugih Subdistrict, Majalengka Regency has an average profit of Rp 28,767,000 per rearing period with R/C and B/C ratio of 2.4 and 1.7, respectively. Meanwhile, the average Break Even Point (BEP) value for each livestock unit is Rp21,785,000 and the average payback period can be achieved in 1 year. It can be concluded that the beef cattle business is financially profitable and economically feasible to run or develop.